Effect of EEG electrode number on epileptic source localization in pediatric patients. Issue 3 (March 2015) - Sohrabpour, Abbas; Lu, Yunfeng; Kankirawatana, Pongkiat; Blount, Jeffrey; Kim, Hyunmi; He, Bin
Highlights The relationship between source localization and electrode number was investigated in pediatric patients with partial epilepsy. Source imaging results were compared with surgical resection and seizure onset zone from intracranial electrodes. The source localization is improved when electrode numbers increase, but the absolute improvement is less significant for larger electrode numbers.